2021
DOI: 10.1186/s12284-021-00464-1
|View full text |Cite
|
Sign up to set email alerts
|

OsPRR37 Alternatively Promotes Heading Date Through Suppressing the Expression of Ghd7 in the Japonica Variety Zhonghua 11 under Natural Long-Day Conditions

Abstract: Heading date is an important agronomic trait of rice (Oryza sativa L.) and is regulated by numerous genes, some of which exhibit functional divergence in a genetic background-dependent manner. Here, we identified a late heading date 7 (lhd7) mutant that flowered later than wild-type Zhonghua 11 (ZH11) under natural long-day (NLD) conditions. Map-based cloning facilitated by the MutMap strategy revealed that LHD7 was on the same locus as OsPRR37 but exhibited a novel function as a promoter of heading date. A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Third, OsCCA1 does not bind to the Ehd1 promoter for floral induction. OsPRR37 and DTH8 are LD-dependent floral repressors that contribute to the generation of robust Ehd1 mRNA oscillations ( Wei et al, 2010 ; Koo et al, 2013 ; Liu et al, 2018 ; Hu et al, 2021 ). Furthermore, since OsPRR37 is epistatic to OsCCA1 ( Supplemental Figure S9 ), it is possible that OsCCA1 induces Ehd1 expression by downregulating OsPRR37 or DTH8 , although further studies are required to verify the molecular mechanisms of OsCCA1 regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, OsCCA1 does not bind to the Ehd1 promoter for floral induction. OsPRR37 and DTH8 are LD-dependent floral repressors that contribute to the generation of robust Ehd1 mRNA oscillations ( Wei et al, 2010 ; Koo et al, 2013 ; Liu et al, 2018 ; Hu et al, 2021 ). Furthermore, since OsPRR37 is epistatic to OsCCA1 ( Supplemental Figure S9 ), it is possible that OsCCA1 induces Ehd1 expression by downregulating OsPRR37 or DTH8 , although further studies are required to verify the molecular mechanisms of OsCCA1 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The components of the circadian clock that are conserved between Arabidopsis and rice are integrated into the photoperiodic flowering network ( Song et al, 2015 ). Among them, we previously showed that rice OsPRR37 , which is orthologous to Arabidopsis PRR7 , suppresses flowering under LD conditions by downregulating Ehd1 and Hd3a expression ( Koo et al, 2013 ; Liu et al, 2018 ; Hu et al, 2021 ). Natural alleles with amino acid (aa) substitutions in the CCT domain of OsPRR37 promote flowering for adaptation to high-latitude regions ( Koo et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The OsPRR37 protein can interact with Ghd8 and NF-YCs, which form an alternative OsNF-Y heterotrimer to affect Hd1-mediated regulation of Hd3a and flowering ( Goretti et al, 2017 ). The distinct role of OsPRR37 in the ZH11 background indicated that OsPRR37 can associate with different partners to perform different functions ( Hu et al, 2021 ). Moreover, the 35 identified differentially methylated DEGs accounted for only a small proportion of DEGs ( Figure 5A ).…”
Section: Discussionmentioning
confidence: 99%
“…OsPRR37 was primarily identified to delay the flowering time and increase grain yield and adaptation in rice ( Koo et al, 2013 ; Liu et al, 2013 , 2015 ; Yan et al, 2013 ; Gao et al, 2014 ; Fujino et al, 2019 ). A recent study further revealed a distinct role of OsPRR37 in promoting flowering in the japonica variety Zhonghua 11 under natural long-day conditions ( Hu et al, 2021 ). Although several output genes involved in the photoperiodic flowering pathway are used to explain the trait variations ( Chen et al, 2021 ; Zhou et al, 2021c ), the underlying mechanism of how OsPRR37 regulates its output genes and multiple traits remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, OsPRR37 could also function as a flowering promoter in cv. Zhonghua 11 (ZH11) background, mainly by inhibited Ghd7 expression ( Hu et al., 2021 ) ( Figure 5C ). Furthermore, OsPRR37 could act as an activator or a suppressor depending on the status of three genes, Ghd7 , DTH8 , and Hd1 ( Zhang et al., 2019 ).…”
Section: Circadian Clock Is Critical To the Inversion Mechanismmentioning
confidence: 99%